Pengaruh Pemasaran Media Sosial dan Kesadaran Merek Terhadap Keputusan Pembelian Produk Maybelline di Kota Palembang - Wijaya, Quincy Riani; Angel, Alycia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the influence of social media marketing and brand awareness on the purchase decisions of Maybelline products. Social media marketing is becoming increasingly important in today's corporate marketing strategies, while brand awareness has a significant role in influencing consumer behavior. The research method used is a survey using questionnaires as a data collection instrument. The sample of this study consisted of potential consumers of Maybelline products who actively use social media. The collected data was then analyzed using multiple linear regression methods to test the research hypothesis.Â Â Â